สภาวะสุขภาพของนักเรียนระดับชั้นประถมศึกษาปีที่ 6 ในโรงเรียนสังกัดเทศบาลทั่วประเทศ - กรรณิกา ดาวไธสง (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The purposes of the research were to study and compare health status of prathom suksa six students from 50 schools under the municipal authority. The constructed questionnaires were sent to 500 students, but only 450 questionnaires, accounting for 90 percent were returned. The data were then analyzed to obstain percentages, means and standard deviations. The t-test was utilized to determine the significant differences at .05 level. One-way analysis of variance and Scheffe test were also applied to test the significant differences. The results revealed as follow : 1. Health status of prathom suksa students were found at normal level. 2. There were no significant differences at .05 in comparing student s health status according to their school sizes. 3. There were significant differences at .05 according to students cleanliness of their bodies and dress, while there were no significant difference at .05 in their mental health.